Investigating the Relationship between Job Compatibility and Controlling Job Stress with Nurses\' Performance: A Case Study on Shiraz State Hospitals 2020 - alireza mosavi; jamaledin alvani (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: Performance is the criterion for judging the effectiveness of individuals, groups, and organizations. The aim of this study was to investigate the relationship between job compatibility and control of job stress with nurses' performance in 2020. Methods: The present study was performed by descriptive-correlation method with applied nature in 2020. The statistical population includes nurses working in Shiraz government hospitals. The sample size was calculated according to the Cochran's formula of 196 nurses and the sampling method was performed in Stratified Sampling. In this study, researchers' self-made questionnaire with three main sections and 13 questions and 5-option Likert scale was used, from completely agreeing to completely disagreeing. Cronbach's alphas reliability was calculated 77.4 in the questionnaire and its validity was obtained using the opinion of experts. Statistical analysis was performed using SPSS22 software and Spearman ,correlation coefficient regression model were used at 0.95 confidence level. Results: The mean and standard deviation of job compatibility variable were 3.368 and 1.15. Job Stress Control variable were 3.084, 1.17 And the performance of nurses variable were 3.408 and 1.02 .There was a significant relationship between job compatibility and performance (r=0.731, p<0.001) and also between stress control and performance (r=0.651 , p<0.001). Conclusion: Job compatibility leads to effective performance of people's duties and a positive attitude towards the new job role which has a positive effect on performance and also reduces high stress and productivity and it causes physical and psychological damage, so by controlling Job stress, personal and organizational performance also improves.